A historical overview of steel tempering parameters. (18th December 2008) - Canale, Lauralice C.F.; Yao, Xin; Gu, Jianfeng; Totten, George E.
The results of the stress relieving and tempering processes are dependent on the temperature and time of the process, which may be correlated using a parameter such as Holloman's (Holloman-Jaffe) parameter or the Larsen-Miller parameter. These parameters are a measure of the thermal effect of the process on the metallurgical transformation of the steel during tempering. The processes that exhibit the same tempering parameter are expected to exhibit the same effect (such as hardness). However, these more traditional numerical expressions assume isothermal tempering processes which seldom exist in production tempering ovens due to the heat-up period prior to soaking at the desired tempering temperature. Although the Larsen-Miller Equation and the Holloman-Jaffe parameter are well-known, their origin and limitations and, in some cases, their use, are often not discussed in detail in most heat treating texts. Therefore, a review of the metallurgy, origin, use and limitations of these expressions is provided here. In addition, recent work describing the development of more precise numerical relationships to describe the tempering process, including non-isothermal tempering processes, is also discussed.